The tadpole of Scinax camposseabrai (Bokermann) (Amphibia, Anura, Hylidae) - Barreto, Gilvana Santos; Del Grande, Maria Lúcia; Napoli, Marcelo Felgueiras; Garda, Adrian Antonio; Juncá, Flora Acuña (Zootaxa, 2019)
The treefrog Scinax camposseabrai (Bokermann) is endemic to the Brazilian semiarid region and known from the municipalities of Maracás, Igaporã and Curaçá, in the state of Bahia, and from the municipality of Matias Cardoso, northern Minas Gerais state, Brazil (Frost 2019). It was removed from the synonymy of Scinax x-signatus (Spix), recognized as a valid species, and placed in the S. ruber clade (sensu Faivovich et al. 2005) by Caramaschi & Cardoso (2006). Taxonomic changes proposed by Duellman et al. (2016) for the genus Scinax were discussed by Lourenço et al. (2016) and Faivovich et al. (2018), and we follow here their suggestion to consider Ololygon and Julianus (erected for the S. uruguayus group) as synonyms of Scinax. This large genus Scinax currently would include 123 species (Frost 2019), many of which have had their larval morphology formerly described. Here, we describe the external morphology of the previously unknown tadpoles of S. camposseabrai.